Psychosocial risks and their predictors in human service occupations: the case of Hungary - Győri, Ágnes; Balogh, Karolina; Ádám, Szilvia; Perpék, Éva (Current Psychology, 2025)
The article investigates similarities and differences in the exposure to psychosocial risk factors among various human service fields. The aim of the research is twofold: firstly, to assess the extent to which the healthcare, social, and education workers are exposed to mental health risk factors compared to other employees in human service professions. Secondly, to determine if there are variations between different areas regarding the types of mental health risk factors encountered by the employees. The research was based on the 2020 Hungarian database of the European Union Labour Force Survey. The analysis was conducted on a subsample of 4,539 individuals aged 15–64 working in human service occupations. Logistic and multinomial regression models were applied in the analysis. Our results indicate that the employees in healthcare, social, and education sectors are more susceptible to mental health risks than those in other human service occupations. Among the most endangered three sectors, healthcare workers face the highest levels of stressors. The most significant stressor is problems related to clients/patients/children. Moreover, the risk of experiencing organizational problems is also elevated in these sectors. The research underscores the importance of regular supervision and mental health support in healthcare, social and education sectors to prevent rapid burnout and turnover intention among employees.